2015
DOI: 10.1186/s12873-015-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening of mental health and substance users in frequent users of a general Swiss emergency department

Abstract: BackgroundThe objectives of this study were to determine the proportions of psychiatric and substance use disorders suffered by emergency departments’ (EDs’) frequent users compared to the mainstream ED population, to evaluate how effectively these disorders were diagnosed in both groups of patients by ED physicians, and to determine if these disorders were predictive of a frequent use of ED services.MethodsThis study is a cross-sectional study with concurrent and retrospective data collection. Between Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 22 publications
1
32
0
4
Order By: Relevance
“…Previous research showed independent associations between frequent visits to the emergency department and physical multimorbidity 7,[9][10][11][12] or mental disorders. 10,11,[13][14][15][16]37 These studies did not distinguish common and serious mental disorders. However, the greater effect of serious mental disorders is consistent with the greater functional disability associated with psychotic and bipolar disorders.…”
Section: Discussionmentioning
confidence: 93%
“…Previous research showed independent associations between frequent visits to the emergency department and physical multimorbidity 7,[9][10][11][12] or mental disorders. 10,11,[13][14][15][16]37 These studies did not distinguish common and serious mental disorders. However, the greater effect of serious mental disorders is consistent with the greater functional disability associated with psychotic and bipolar disorders.…”
Section: Discussionmentioning
confidence: 93%
“…Individuals with multiple co-occurring MDs and SUDs, similar to our class 2, were more likely to have high emergency department use. 22,32,56 Studies also found associations between high emergency department use and specific diagnoses, such as schizophrenia, [22][23][24] bipolar disorder, 33 depression, 33,59 personality disorder, 22,25,26,28 anxiety 23,24,26,33 and alcohol and drug use disorders. 4,22,23,29 Moreover, individuals from class 2 were frequently admitted to hospital and made more frequent visits to psychiatrists than others (enabling factors).…”
Section: Discussionmentioning
confidence: 99%
“…age, gender, education, employment and household income); and enabling factors refer to variables that facilitate access or continuity in health services, such as having a regular source of care. 21 The main needs factors identified in association with higher frequency of emergency department use for mental health reasons are mental health diagnoses, including schizophrenia, [22][23][24] personality disorder 22,[24][25][26][27][28] and SUDs, 4,22,23,29 as well as co-occurring MD-SUD and/or chronic physical illnesses. 22,[30][31][32] Regarding predisposing factors, an association was found between higher frequency of emergency department use and male gender, 18,29,30 whereas the association between emergency department use and age categories was not consistent.…”
mentioning
confidence: 99%
“…3 Common reasons for such frequent use include pain, chronic physical and mental illness, and substance abuse. 1,2,4,5 Frequent ED users are mainly men, are between 40 and 50 years of age, are sicker and have higher rates of mortality than occasional ED users. 1,2,6 As such, they merit focused attention, and research on interventions to meet their needs is needed.…”
Section: Introductionmentioning
confidence: 99%